Safety, Tolerability, and Immunogenicity of Revaccination with mRNA-1345, an mRNA Vaccine Against RSV, Administered 12 Months Following a Primary Dose in Adults Aged ≥50 Years - Goswami, Jaya; Cardona, Jose F; Caso, Jorge; Hsu, Denise C; Simorellis, Alana K; Wilson, Lauren; Dhar, Rakesh; Wang, Xiaowei; Kapoor, Archana; Collins, Avi; Righi, Vinicius; Lan, Lan; et al. (Clinical infectious diseases, 2025)
mRNA-1345 is a respiratory syncytial virus (RSV) vaccine approved for prevention of RSV-associated lower respiratory tract disease in individuals ≥60 years. Durability of efficacy is being evaluated in clinical trials. Data on revaccination in adults are needed. This open-label, phase 3 trial evaluated revaccination with 50-µg mRNA-1345 administered 12 months after primary vaccination in participants aged ≥50 years. The primary objectives were the immunogenicity (RSV-A and RSV-B neutralizing antibody [nAb] responses), tolerability, and safety of revaccination. 543 participants were revaccinated. Most adverse reactions were mild/moderate (median duration, 2 days), with no new safety concerns identified. Co-primary immunogenicity endpoints met pre-specified non-inferiority criteria based on Day 29 geometric mean titer ratios (GMRs; revaccination vs primary vaccination). At Day 29, nAb GMRs (95% CI) were 1.08 (1.0-1.17) for RSV-A and 0.91 (0.84-0.98) for RSV-B. Seroresponse rates (≥4-fold rise from baseline; 95% CI) at Day 29 were 77.5% (73.7-81.0) for RSV-A and 47.5% (43.2-51.9) for RSV-B, with a ≥2-fold rise in titers observed in 91.6% (88.9-93.8) and 69.8% (65.7-73.8) of participants, respectively. Following primary vaccination, RSV nAb titers increased by Day 29 and gradually declined over 12 months, yet remained above baseline levels. Revaccination at 12 months increased nAb titers, similar to the response observed after the primary dose. Revaccination of adults ≥50 years with mRNA-1345 was well-tolerated with a safety profile consistent with the primary dose. RSV nAb at Day 29 were non-inferior to those after a primary mRNA-1345 dose, with antibody response persisting for 12 months. ClinicalTrials.gov: NCT05330975.